COUNTER ACTIVITY OF PROBIOTICS WITH REFERENCE TO PATHOGENIC BACTERIA - S.SREEVANI; J. PRAMODA KUMARI (International Journal of Pharma and Bio Sciences, 2013)
Most of the microbes play a vital role in health benefits, probiotics are one of them. In this study fL. plantarum- MTCC2621 gives more yields but incase of Bile salt tolerance assayL. rhamnosus- MTCC-1408 gives more yield. L. rhamnosus- MTCC-1408, L. delbrueckii-MTCC-911, L. fermentum-MTCC-903, L. plantarum- MTCC2621 gives more yields but incase of Bile salt tolerance assayL. rhamnosus- MTCC-1408 gives more yield. L. rhamnosus- MTCC-1408, L. delbrueckii-MTCC-911, L. fermentum-MTCC-903, L. plantarum- MTCC2621 inhibits Bacillus subtilisand Staphylococcus aureusmore efficiently than E. coli and Pseudomonas aeruginosa.